Case report: Endovascular treatment of acute limb ischemia in an adolescent with newly diagnosed lupus - Liu, Lu-Hang; Lee, Ming-Dar; Huang, Ting-Huan; Chu, Szu-Hung; Hsieh, Mu-Yang (Frontiers in Cardiovascular Medicine, 2023)
We report a 14-year-old adolescent who presented with acute limb ischemia caused by systemic lupus erythematosus-related antiphospholipid syndrome (APS). In the pediatric population, acute limb ischemia is rare. This case is unique in that after the initial medical treatment failed, interventional devices for acute stroke intervention were utilized to salvage the limb in our patient with a small tibial artery vessel to achieve procedural success. To provide limb salvage, operators may combine peripheral and neuro-intervention devices to maximize procedure success.